The Analysis of Education Based on Ethnopedagogy in Forming Characters of 4th Grade Students in SDN 115 Pekanbaru - Tity Hastuti; Zaka Hadikusuma Ramadan (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
This research aims to; 1) describe ethnopedagogy learning in SDN115 Pekanbaru; 2) describe the formation of character in SDN 115 Pekanbaru; 3) describe what characters are formed for students in SDN 115 Pekanbaru; and 4) describe the factors that inhibit the implementation of character building through ethnopedagogy in SDN 115 Pekanbaru. This research uses a qualitative approach. The method used in this research is naturalistic inquiry. The sample of this research consisted of 1 Headmaster and 3 teachers from class IV. The location of research study was conducted in SDN 115 Pekanbaru. Data collection techniques in this research are; 1) interview; 2) observation; and 3) documentation. Data analysis of the research results used Miles and Huberman model, namely, data reduction, data display, drawing conclusion. Ethnopedagogy in SDN 115 is carried out with many programs, starting with the curriculum, namely the existence of Arabic Malay subject matter, and the existence of the obligatory study for 15 minutes before class time and the existence of Imtaq activities on every Friday. In addition, the latest program is the subject of Riau Malay Culture (BMR) which is an instruction from the Mayor of Pekanbaru as a means of preserving Riau's Malay culture to students. The process of habituation such as smiles and greetings is a routine activity every morning for teachers waiting in front of the gate to welcome students. Saying greetings when you meet is something that has been entrenched in SDN 115 Pekanbaru. In addition there are some words such as pointing Malay teaching that is posted on the school wall, which is essentially for students to see, to read and to remember. The characters developed in ethnopedagogy-based learning are religious, honest, diligent, disciplined, and caring/responsible. Related to the implementation and obstacles encountered and the solutions pursued by SDN 115 Pekanbaru in the implementation of ethnopedagogy. As for the obstacles including, accustoming students to love the environment, uniting the perspective and the purpose of classroom action research, students, and parents, disciplining students to arrive on time, lack of teaching materials in the form of BMR material. The solution sought by SDN 115 Pekanbaru is to keep trying to get used to, give examples, give advice, and provide guidance.